Social Support as a Moderator of the Relationship between Financial Threat and Life Satisfaction - Matavelli, Rafaela Dias; Jesus, Saul Neves de; Pinto, Patrícia; Viseu, João (Journal of Tourism, Sustainability and Well-being, 2020)
Financial crises often lead to an increase of pathological symptoms which have a negative impact on life satisfaction. This study analysed the moderating role of social support on the relationship between perceived financial threat and life satisfaction, during austerity periods. Structural equation modelling (SEM) using multiple-group analysis was used to assess the obtained results. The collected sample was composed by 901 Portuguese individuals, 603 females and 298 males, with an average age of 37 years old. Overall, results indicated a model in which perceived financial threat and social support were negatively and positively associated with life satisfaction, respectively. The moderating effect of social support revealed that in the group with the highest level of support there was a significant decrease in the association between perceived financial threat and life satisfaction, i.e., social support mitigated the negative effects of perceived financial threat on life satisfaction. The implications of these results are discussed.